Production of β-fructofuranosidase by Arthrobacter sp. and its application in the modification of stevioside and rebaudioside A - Xu, Zhong-Wei (Array, 2009)
Arthrobacter sp. 10137 has been used to produce β-fructofuranosidase (FFase). Sucrose and corn steep powder in an optimized ratio of 10:1 were the best carbon and nitrogen sources for enzyme production in a shake flask. The maximum FFase activity was 26.69 U/mL after 22.5 h in batch culture, and the crude FFase, obtained by ultrafiltration and (NH4)2SO4 fractionation, was purified about 7-fold as measured by specific activity from the crude culture filtrate. The FFase was specific for introduction of a fructose molecule at the C19 position on both the stevioside and rebaudioside A, with high transfructosylating activity of 65 % after 15 h of incubation.